A fonética forense no Brasil : cenários e atores - Gomes, Maria Lúcia de Castro; Carneiro, Denise de Oliveira (Language and Law / Linguagem e Direito, 2017)
Forensic phonetics is a very recent area, especially in Brazil, which, like any other Veld that makes use of technological resources, is always in need of consistent research projects. Multidisciplinary par excellence forensic phonetics is a discipline that uses knowledge from many other disciplines and utilizes professionals from diUerent specialties. The purpose of this article, though, is not to present any research results or theoretical argumentation. Rather the paper aims to present an overview of forensic phonetics in Brazil. It starts with a discussion of the terminology adopted by researchers and experts, followed by a presentation of the main places where research in forensic phonetics is being undertaken. After that, it presents the state of the art in Brazil, including the forensic expertise available to the Brazilian judicial system, the institutions that provide the expertise, and the associations and publications in the area. Finally, the need for greater involvement by universities in discussion about and research into forensic phonetics will be discussed, focusing always on multidisciplinarity.